2019
DOI: 10.1093/isq/sqz020
|View full text |Cite
|
Sign up to set email alerts
|

Blue Helmets, Red Flags: Institutional, Societal, and Military Determinants of Peacekeeping Abuses

Abstract: United Nations peacekeeping soldiers commit atrocities while deployed despite their mandate to protect civilians from harm. Yet, there is tremendous variation across missions in reported human rights abuses. Why are some missions more susceptible to misconduct than others? To answer this puzzle, we identify three broad sources of influence on peacekeeper behavior: institutions, society, and military culture. Using newly collected data, we find that host-country and contributing-country institutions, particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Since the first reports of the early 1990s, almost all PSO have been associated with sexual misconduct to some degree of magnitude and severity (Lee 2017). Different missions have raised different concerns, and recent academic scholarship has led to some understanding of the factors underlying SEA within the context stability of peacekeeping economies around bases (Jennings and Bøås 2015;Jennings 2015;Rodriguez and Kinne 2019) including the economic power differentials between members of the local population and PSO personnel (Bell, Flynn, and Machain 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Since the first reports of the early 1990s, almost all PSO have been associated with sexual misconduct to some degree of magnitude and severity (Lee 2017). Different missions have raised different concerns, and recent academic scholarship has led to some understanding of the factors underlying SEA within the context stability of peacekeeping economies around bases (Jennings and Bøås 2015;Jennings 2015;Rodriguez and Kinne 2019) including the economic power differentials between members of the local population and PSO personnel (Bell, Flynn, and Machain 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Marisella Rodriguez, Brandon J Kinne has found that to a significant extent the freedom of press and the reign of law dramatically reduce the number of offenses [3]. I.V.…”
Section: Introductionmentioning
confidence: 99%